Изменение места и роли коммуникации в современном мире - Барматова, С. (Iнститут соціології НАН України, 2009)
In the modern society, we observe crucial changes correlated with transformations in the communication and information spheres. How do they influence development and functioning of all social sys tem? Can they be come the reason of transformation of the major social system? To what extent the laws of information and communication do influence the laws of social institutes functioning? And can they influence transformation of such traditional systems as mass-media, man, and social space as a whole? The changes which occur to the information and communications in the modern society have both positive and negative consequences. They do not bear the threat to social system. Rather they highlight the special moments of process of its transformation toward a qualitatively new level of functioning and take part in formation of new (network) design of social space. This problem has not yet been sufficiently elucidated within sociological studies. So the theme requires careful elaboration.